High Flow Oxygen Therapy in Patients with Burn Injury - А. А. Ponomarev; V. V. Kazennov; А. N. Kudryavtsev; А. V. Korneev; А. А. Аlekseev (Вестник анестезиологии и реаниматологии, 2021)
Some patients with severe burn injury have a high risk of developing acute respiratory failure, the cause of which may be interstitial pulmonary edema caused by inadequate infusion therapy.The objective: to evaluate the effectiveness of high-flow oxygen therapy (HFOT) in acute parenchymatous respiratory failure in burn patients.Subjects and methods. The prospective analysis included 74 patients with ARF in the stage of burn toxemia, without inhalation trauma, with PaO2/FiO2 below 300. In Main Group (37 patients), HFOT was used, while in Control Group patients received oxygenation through nasal cannula with the rate up to 15 l/min. Parameters of respiratory rate, PaO2/FiO2, PaCO2, MAP, heart rate, the number of intubations, respiratory comfort were recorded within 48 hours.Results. Main Group had higher values of oxygenation index in 48 hours of the trial (342 vs. 305.5, p = 0.02), faster normalization of blood gas composition compared to Control Group. HFOT was associated with greater respiratory comfort (8.4 vs. 5.3 VAS scores, p = 0.03), lower need in mechanical ventilation (4 vs. 11, p = 0.04).Conclusion: HFOT is an effective method for the treatment of respiratory failure in inpatients with burns. The need for intubation decreases, it is more comfortable to be tolerated than standard methods of oxygen therapy.